2016
DOI: 10.3847/0004-637x/829/2/118
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Internal Structure of Jupiter and Saturn With Compositional Gradients

Abstract: The internal structure of gas giant planets may be more complex than the commonly assumed core-envelope structure with an adiabatic temperature profile. Different primordial internal structures as well as various physical processes can lead to non-homogenous compositional distributions. A non-homogenous internal structure has a significant impact on the thermal evolution and final structure of the planets. In this paper, we present alternative structure and evolution models for Jupiter and Saturn allowing for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 37 publications
10
109
0
Order By: Relevance
“…However, the primordial distribution of heavy elements could change during the planetary long-term evolution due to core erosion and/or convective mixing (e.g., Guillot et al 2004;Wilson & Militzer 2012;Vazan et al 2016). We suggest that the mass and composition of giant planet cores depend on their exact formation history.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the primordial distribution of heavy elements could change during the planetary long-term evolution due to core erosion and/or convective mixing (e.g., Guillot et al 2004;Wilson & Militzer 2012;Vazan et al 2016). We suggest that the mass and composition of giant planet cores depend on their exact formation history.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…Note that this is different from the model of Lozovsky et al (2017), where the regions with composition gradients that were found to be convective according to the Ledoux convection criteria were assumed to homogenize instantaneously due to mixing. However, homogenizing convective regions with composition gradients requires a fairly long time 10 10 years 7 9  -formation timescale (see Vazan et al 2016). The exact timescale depends on the mixing model, particularly, on the mixing length when using mixing length theory.…”
Section: Jupiter's Primordial Internal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This is because it is currently unclear whether a centrally concentrated distribution of heavy elements (in a solid core or a strongly enriched inner region) at the beginning of detachment could shift to a more homogeneous distribution over time as heavy elements are soluble in H/He under conditions typical for giant planet interiors (e.g., Soubiran & Militzer 2015), or alternatively, that heavy elements sink over long timescale to the center. The results of Vazan et al (2016) indicate that no full mixing occurs if the initial compositional gradient is strong enough. If the heavy element mass fraction as a function of enclosed mass Z(M) in a planet today (see the Juno spacecraft data, Wahl et al 2017) therefore reflects at least partially the structure during build-up, this would open an interesting avenue to constrain the ratio of the solid accretion to the gas accretion rate as a function of planet mass,Ṁ Z /Ṁ XY (M).…”
Section: Uncertainties Related To the Core-mass Effectmentioning
confidence: 76%
“…For the other two, namely Saturn which is brighter relative to these models by about 60% ) and Uranus which is fainter by at least one order of magnitude (Guillot & Gautier 2014), additional physical effects must play a role that we do not consider here. These effects could be: a demixing of different chemical species followed by gravitational settling causing a net rearrangement of matter like a helium rain, which could explain Saturn (Stevenson & Salpeter 1977), compositional gradients (e.g., Vazan et al 2016) that can lead to semiconvection and nonadiabatic interiors, which could explain both Saturn (Leconte & Chabrier 2013) and Uranus , and finally core erosion where a part of the planet's luminosity is used to dredge up core material (e.g., Guillot et al 2004). …”
Section: Simplifications and Limitations Of The Internal Structure Modelmentioning
confidence: 99%